The Role of Moderation In Islamic Jurisprudence According To Al-Alusi And His Interpretation As A Model - Muhammad Firdaus; Fitriana Fitriana (Penerbit dan Percetakan CV. Picmotiv, 2026)
This research, in its modest form, attempts to delve into what Al-Alusi explained about the concept of moderation, which is a mainstay in Islamic jurisprudence, through his interpretation titled